A new sensor inspired by the lateral-line system of fish using the self-powered d33 mode piezoelectric diaphragm for hydrodynamic sensing. (July 2020) - Zhang, Xingxu; Shan, Xiaobiao; Xie, Tao; Miao, Jianmin
Highlights: A sensor consisted of a d33 mode PZT diaphragm and a pillar was designed. Finite element analysis was conducted to estimate the behavior of the sensor. Impedance spectrums were examined after prototypes were fabricated. Underwater experiments were carried out and demonstrated a high sensitivity. Abstract: Inspired by the ubiquitous lateral-line system of fish which plays an essential role in flow sensing and object detection, this paper presents a new sensor consisting of a radial field piezoelectric diaphragm in d33 mode and a high aspect ratio pillar. Finite element analysis was conducted to simulate the in-plane poling released by inter-circulating electrodes and the vibration behavior of the sensor. Prototypes were fabricated by microfabrication combined with 3D printing. Impedance spectrums were examined to characterize the dynamic behaviors of the sensor. By utilizing a vibrating sphere to imitate the underwater disturbances, the performance of the sensor in sensing oscillatory flows was tested. Experimental results demonstrate that the sensor has a high sensitivity of 2.476 mV/(mm/s) and very good response ability to the low frequency hydrodynamic flow phenomena. Besides, the ability of the sensor in locating the vibrating sphere was illustrated. This sensor is miniaturized, light-weight, self-powered and low-cost. It provides a good prospect for the underwater sensing of autonomous underwater vehicles.